2020
DOI: 10.1177/2048872619883399
|View full text |Cite
|
Sign up to set email alerts
|

Early signs of right ventricular systolic and diastolic dysfunction in acute severe respiratory failure: the importance of diastolic restrictive pattern

Abstract: Background: The incidence and pathophysiology of right ventricular failure in patients with severe respiratory insufficiency has been largely investigated. However, there is a lack of early signs suggesting right ventricular systolic and diastolic dysfunction prior to acute cor pulmonale development. Methods: We conducted a retrospective analytical cohort study of patients for acute respiratory distress syndrome undertaking an echocardiography during admission in the cardiothoracic intensive care unit. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…4 ) ( Vieillard-Baron et al, 2013 ; Boissier et al, 2013 ; Chiumello and Pesenti, 2013 ). This coupling between the pulmonary vasculature and the right ventricle was particularly important in ARDS induced by more vascular inflammation as experienced globally during the coronavirus pandemic ( Patel et al, 2020 ; Ridge et al, 2020 ; Tavazzi et al, 2019 ; Bleakley et al, 2020 ).
Fig.
…”
Section: Progression Of Ardsmentioning
confidence: 99%
“…4 ) ( Vieillard-Baron et al, 2013 ; Boissier et al, 2013 ; Chiumello and Pesenti, 2013 ). This coupling between the pulmonary vasculature and the right ventricle was particularly important in ARDS induced by more vascular inflammation as experienced globally during the coronavirus pandemic ( Patel et al, 2020 ; Ridge et al, 2020 ; Tavazzi et al, 2019 ; Bleakley et al, 2020 ).
Fig.
…”
Section: Progression Of Ardsmentioning
confidence: 99%
“…6 Right ventricular diastolic dysfunction is common in patients with ARDS in the absence of RV dilatation; it is therefore important to consider that increases in pulmonary vascular resistance, will also adversely affect diastolic function and possibly earlier than that demonstrated on systolic assessment. 13 Assessment of RV diastolic function (morphological assessment of the inferior vena cava, doppler interrogation of tricuspid inflow, tissue doppler at the lateral tricuspid annulus, and pulsed wave doppler sampling of hepatic vein flow) should be considered and included in future clinical prediction models determining RV injury risk in ARDS. 14 A recent observational study exploring myocardial phenotypes and clinical associations of RV dysfunction in COVID-19 ARDS showed that severe COVID-19 ARDS is associated with a specific phenotype characterized by radial impairment with sparing of longitudinal function.…”
Section: Early Diagnosis and Real-time Monitoringmentioning
confidence: 99%
“…Although the effects of respiratory function against cardiac function have already been reported [27][28][29], there were few studies investigating the relationship between smoking exposure and cardiac function, after adjusting for respiratory function. In the present study, the higher the participants' smoking exposure, the larger the values of FVC and VC.…”
Section: Table 2 Echocardiographic Characteristics Of Participants Acmentioning
confidence: 99%